Beyond Bell's Palsy: Cephalic Tetanus Unveiled - Lubna Khan; Samra Mansoori; Raeda Khan; Mohammad Iqbal (Pakistan Journal of Medicine and Dentistry)
Tetanus, although rare in vaccinated regions, remains common in developing countries. Cephalic tetanus, caused by Clostridium tetani, is a rare, potentially fatal neurological condition. The presenting symptoms include spasms, rigidity, and paralysis in the head and neck. This case report describes a 5-year-old girl with unilateral facial paralysis initially diagnosed as Bell's palsy. Subsequent development of trismus and dysphagia led to a revised diagnosis of cephalic tetanus. Peripheral facial palsy may be an early sign of cephalic tetanus and should be considered in patients with relevant exposure history. Our patient’s recent nasal foreign body removal raised suspicion of cephalic tetanus, confirmed through clinical findings. Treatment with tetanus immunoglobulin and antibiotics led to gradual improvement. This case emphasizes the importance of considering cephalic tetanus in the differential diagnosis of facial nerve palsy, especially if there is a history of foreign body exposure. Early recognition and treatment are essential for favorable outcomes.